Optimization of Local Wisdom-Based Ecotourism as a Pillar of Sustainable Green Tourism in Kledung District, Temanggung Regency - Yustina Denik Risyanti; Mengku Marhendi; Trenggono Trenggono; Rizal Nikko Saputra; Elia Nicholas Tegar Isakhar (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
Research on sustainable tourism in Kledung, Central Java, plays a crucial role, especially in today’s modern era, where environmental conservation and local community empowerment have become top priorities. With the rapid development of the tourism sector, it is necessary to identify and implement development models aligned with the principles of sustainable tourism and the preservation of local wisdom to achieve long-term sustainability. The roles of the central government, local government, and tourism business stakeholders are also essential in realizing sustainable tourism. Kledung District, located at the foot of Mount Sindoro and Mount Sumbing, holds significant potential to be developed as a green tourism destination by integrating natural beauty, cultural richness, and local wisdom. The aim of this research is to optimize the tourism potential of Kledung through an ecotourism and sustainable green tourism approach rooted in local wisdom. By utilizing the area's natural wealth and strong cultural traditions, Kledung is envisioned as an environmentally friendly tourism destination. As stated by, environmentally conscious sustainable development and improvement are necessary to ensure the preservation of resources and that the benefits can be enjoyed by both present and future generations. Furthermore, emphasizes that ecotourism empowers local communities to preserve their traditions and culture while also gaining economic benefits from tourism activities. The concept of ecotourism will be integrated with sustainability principles, focusing not only on environmental conservation but also on local community empowerment and social welfare improvement. This study analyzes the natural and cultural potential as well as the environmental impacts of tourism to ensure sustainability. Supporting the view of , the economic aspect of sustainable tourism includes sustainable income and community involvement in cultural preservation. The research is expected to provide recommendations for more effective and sustainable tourism development in Kledung, along with an innovative and inclusive tourism management mode. The aim of this research is to optimize the tourism potential of Kledung through an ecotourism and sustainable green tourism approach rooted in local wisdom. By utilizing the area's natural wealth and strong cultural traditions, Kledung is envisioned as an environmentally friendly tourism destination. As stated by [2], environmentally conscious sustainable development and improvement are necessary to ensure the preservation of resources and that the benefits can be enjoyed by both present and future generations. Furthermore, [3] emphasizes that ecotourism empowers local communities to preserve their traditions and culture while also gaining economic benefits from tourism activities. The concept of ecotourism will be integrated with sustainability principles, focusing not only on environmental conservation but also on local community empowerment and social welfare improvement. This study analyzes the natural and cultural potential as well as the environmental impacts of tourism to ensure sustainability. Supporting the view of [4], the economic aspect of sustainable tourism includes sustainable income and community involvement in cultural preservation. The research is expected to provide recommendations for more effective and sustainable tourism development in Kledung, along with an innovative and inclusive tourism management mode